Hungarian Monitoring, 6 December 1989 . [Magyar rádiófigyelő], 1989. december 6 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Yugoslav-Romanian relations - Romanian national minorities policy: interview with Ceauşescu - Soviet-French summit - Financial and trade scandals in the GDR Domestic Affairs: - Mátyás Szűrös's letter to N. Ceauşescu - Political Discussion Committee formed - Questions of education policy - Problems at Budapest Public Transport Company - Election Alliance of the Turul People formed - No election alliance between Hungarian Socialist Party (MSZP) and Hungarian Socialist Workers' Party (MSZMP) Economy: - IMF talks and loans - Rába factory in Győr Külpolitika: - A jugoszláv-román kapcsolatok - A román nemzetiségi politika - Interjú Ceauşescuval - A szovjet-francia csúcstalálkozó - Az NDK-beli pénzügyi, külkereskedelmi botrányok Belpolitika: - Szűrös Mátyás levele N. Ceauşescuhoz - Megalakult a Politikai Egyeztető Bizottság - Oktatáspolitikai kérdések - BKV gondok - Megalakult a Turul Népe Választási Szövetség - Nem lesz választási szövetség az MSZP és az MSZMP között Gazdaság: - Valutalap tárgyalások, hitelek - Győri Rába Gyár